Factors influencing satisfaction of the quality of antenatal care services in health facilities in Lusaka district: a cross-sectional study - Mwanja, Melody Mudenda; Kazonga, Eustarckio (International Journal Of Community Medicine And Public Health, 2022)
Background: Patient satisfaction in antenatal care (ANC) service delivery comes from good patient outcomes and the good quality of care that a patient receives. The objective of this study was to determine factors influencing the quality of ANC services in health facilities in Lusaka District in Zambia. Methods: A quantitative approach with a cross-sectional study design was used. The sample size was drawn from 20 public and private. From these institutions, a random sample of 385 participants (expectant mothers) was selected. Furthermore, 40 care-givers were selected as key informants. The questionnaires and interviews were employed to collect data. The data was analysed by performing factor analysis, correlation analysis and multiple regression analysis using statistical package for social sciences (SPSS) 16.0. Results: There was a strong positive correlation between the variables: quality of ANC service and patient satisfaction, the relationship was not very strong as most of the dimensions of ANC were influencing satisfaction slightly above 60%. The empathy dimension was regarded to be the major predictor as it was rated highly in influencing for satisfaction with a Cronbach’s alpha score of above 0.8. However, the cost of service showed a strong negative correlation in relation to satisfaction. Conclusions: The study concludes that ANC services provision has an influence on the expectant mothers’ satisfaction. Different dimensions of antenatal care services influence satisfaction differently and a combination of several dimensions posts increased satisfaction.